A Human Machine Interface (HMI) Framework for Smart Grid System - Ab Ghani, Mohd Ruddin; Raman, Siti Hajar; Mat Hanafiah, Mohd Ariff; Wan Jusoh, Wan Nor Shela Ezwane (2014)
Smart Grid is a progressively important function in the electricity delivery system. Smart grid is requiring increasingly refined communication media. The system described in this paper consists of a human machine interface (HMI) which will monitor various physical activities that occur at Smart Grid. The HMI is designed using SCADA package software. The proposed system is using GSM as communication media that has the benefits of being simple in its scheme which supports to the complete low cost. The originality of the work lies in the low cost method. The proposed system is capable of transferring and receiving signals with the additional advantages of response tool.